New Gerbera Daisy Varieties for Large Containers and Flower Gardens - Zhanao Deng (EDIS)
ENH1170, a 6-page illustrated fact sheet by Zhanao Deng, describes six new varieties of this popular brightly colored flower that have been released recently by the UF/IFAS gerbera breeding program — descriptions, powdery mildew resistance, availability, greenhouse production, and plant care in large containers or flower gardens. Includes references. Published by the UF Department of Environmental Horticulture, July 2010.